Simulation of thermal stress in Er2O3 and Al2O3 tritium penetration barriers by finite-element analysis - 刘泽 汪渊 余国刚 何安平 王玲 (Plasma science & technology, 2017)
The physical vapor deposition method is an effective way to deposit Al2O3 and Er2O3 on 316 L stainless steel substrates acting as tritium permeation barriers in a fusion reactor. The distribution of residual thermal stress is calculated both in Al2O3 and Er2O3 coating systems with planar and rough substrates using finite element analysis. The parameters influencing the thermal stress in the sputter process are analyzed, such as coating and substrate properties, temperature and Young＇s modulus. This work shows that the thermal stress in Al2O3 and Er2O3 coating systems exhibit a linear relationship with substrate thickness, temperature and Young＇s modulus.However, this relationship is inversed with coating thickness. In addition, the rough substrate surface can increase the thermal stress in the process of coating deposition. The adhesive strength between the coating and the substrate is evaluated by the shear stress. Due to the higher compressive shear stress, the Al2O3 coating has a better adhesive strength with a 316 L stainless steel substrate than the Er2O3 coating. Furthermore, the analysis shows that it is a useful way to improve adhesive strength with increasing interface roughness.